ORIGINAL PAPER Bacterial burden of the patients with coronary artery disease treated surgically with coronary artery bypass grafting - Jegier, Bogdan; Jander, Sławomir (Archives of Medical Science, 2005)
Background: Infection with Chlamydia pneumoniae , Helicobacter pylori and Mycoplasma pneumoniae is taken into consideration as a factor influencing development of atherosclerosis. Objective: The aim of the study was an assessment of infectious burden with selected bacterial microorganisms in the patients with advanced atherosclerotic process. Material and methods: The study included 40 patients with three-vessels stable coronary arteries disease referred to the surgical revascularization. Plasma levels of IgG class antibodies anti- Chlamydia pneumoniae , anti- Helicobacter pylori and anti- Mycoplasma pneumoniae were determined with the tests based on the ELISA technique (Enzyme linked Immunosorbent Assay). Results: In the study group, plasma IgG class antibodies anti- Helicobacter pylori (n=35, f=0.875, p<0.05) and a combination of antibodies anti- Helicobacter pylori and anti- Chlamydia pneumoniae (n=17, f=0.81, p<0.001) were significantly more frequently detected in comparison with the other antibodies. Conclusions: The results of the study may suggest a participation of bacterial factor in the atherosclerotic process developing in coronary arteries. In stable advanced three-vessels coronary arteries disease the infection with two kinds of pathogens was significantly more frequently detected. However, our findings did not allow to determine a role of bacterial infection in etiopathogenesis of atherosclerosis